2022
DOI: 10.1038/s41467-022-34097-9
|View full text |Cite
|
Sign up to set email alerts
|

A distinct mammalian disome collision interface harbors K63-linked polyubiquitination of uS10 to trigger hRQT-mediated subunit dissociation

Abstract: Translational stalling events that result in ribosome collisions induce Ribosome-associated Quality Control (RQC) in order to degrade potentially toxic truncated nascent proteins. For RQC induction, the collided ribosomes are first marked by the Hel2/ZNF598 E3 ubiquitin ligase to recruit the RQT complex for subunit dissociation. In yeast, uS10 is polyubiquitinated by Hel2, whereas eS10 is preferentially monoubiquitinated by ZNF598 in human cells for an unknown reason. Here, we characterize the ubiquitination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 49 publications
7
45
1
Order By: Relevance
“…In the first step, the RQT is recruited to the ribosome queue after Hel2-dependent K63-linked uS10 polyubiquitination via interaction with the CUE domain of the Cue3 subunit 12 , 22 , 46 , 47 . After recruitment, RQT stably locks onto the 40S of the stalled/lead ribosome in the C1 conformation via the Slh1 NTC, placing the Slh1 CTC in a position primed to bind the 3′ region of the mRNA emerging from the ribosomal mRNA entry site.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, the RQT is recruited to the ribosome queue after Hel2-dependent K63-linked uS10 polyubiquitination via interaction with the CUE domain of the Cue3 subunit 12 , 22 , 46 , 47 . After recruitment, RQT stably locks onto the 40S of the stalled/lead ribosome in the C1 conformation via the Slh1 NTC, placing the Slh1 CTC in a position primed to bind the 3′ region of the mRNA emerging from the ribosomal mRNA entry site.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that ZNF598 functionally marks collided mammalian ribosomes by K63-linked polyubiquitination of uS10 for the trimeric hRQT complex-mediated subunit dissociation, 16 indicating that the crucial role of K63-linked ubiquitination of uS10 for the RQT-mediated clearance is conserved in eukaryotes from yeast to mammals. Since the trimeric hRQT complex is composed of ASCC3 (Slh1), ASCC2 (Cue3), and TRIP4 (Rqt4), the conservation of the mechanism for K63-linked ubiquitin recognition by TRIP4 should be investigated in the future work.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent translation arrest results in ribosome collision, which is considered a hallmark of translational stress. [1][2][3][4][5][6][7] Several sensor proteins recognize ribosomal collision and induce different cellular responses, including the ribosome-associated quality control (RQC) pathway, [8][9][10][11][12][13][14][15][16] no-go decay (NGD), [17][18][19] the integrated stress response (ISR), [20][21][22][23][24][25] and the ribotoxic stress response (RSR). 21,[26][27][28] The RQC pathway is the rescue system for stalled ribosomes, thereby contributing to the clearance of collided ribosomes to decrease the severity of translational stress.…”
mentioning
confidence: 99%
“…Anisomycin treatment increases the ZNF598-mediated ubiquitination of uS10 and eS10 and their disome formation (50)(51)(52)(53) and also increases ufmylation, suggesting that ufmylation is required for ER-RQC. We examined the role of the UFL1-UFBP1-CDK5RAP3 E3 complex in RQC-mediated degradation of nascent polypeptides derived from stalled ribosomes.…”
Section: Association Of the E3 Ufm1 Complex With The 60s Ribosomal Su...mentioning
confidence: 99%